2015
DOI: 10.1103/physrevb.91.195438
|View full text |Cite
|
Sign up to set email alerts
|

Resonant transport and electrostatic effects in single-molecule electrical junctions

Abstract: In this contribution we demonstrate structural control over a transport resonance in HS(CH 2 ) n [1,4 − C 6 H 4 ](CH 2 ) n SH (n = 1, 3, 4, 6) metal-molecule-metal junctions, fabricated and tested using the scanning tunneling microscopy-based I (z) method. The Breit-Wigner resonance originates from one of the arene π -bonding orbitals, which sharpens and moves closer to the contact Fermi energy as n increases. Varying the number of methylene groups thus leads to a very shallow decay of the conductance with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
(108 reference statements)
2
28
0
Order By: Relevance
“…Peaks in the histograms were fitted to a Gaussian distribution to determine the most probable conductance, expressed in nS. Data for the X[Ph]X class of molecular wires was taken after Brooke et al, 41 and data for the alkanedithiol series was taken from Haiss et al 29 The experimentally determined conductance values were then plotted as ln(G) vs. length, and a linear fitting was used to obtain the β′ attenuation and its standard deviation is used as error.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peaks in the histograms were fitted to a Gaussian distribution to determine the most probable conductance, expressed in nS. Data for the X[Ph]X class of molecular wires was taken after Brooke et al, 41 and data for the alkanedithiol series was taken from Haiss et al 29 The experimentally determined conductance values were then plotted as ln(G) vs. length, and a linear fitting was used to obtain the β′ attenuation and its standard deviation is used as error.…”
Section: Resultsmentioning
confidence: 99%
“…14,23,[35][36][37][38][39][40] They have improved our understanding of the conductance decay with length in MMM junctions, but the effect of the molecular wire structure on the value of β is still not completely understood. An important feature in the transport characteristics of alkanedithiols is the presence of a broad resonance, called in previous studies a "gateway state" 41 or "contact-level", 30 close in energy to the Fermi level of the metallic leads. In a systematic study of alkane molecular junctions with gold electrodes, Kim et al, reported a small peak close to the Fermi energy and a broad one about −1 eV from the Fermi energy, and they showed that the resonances are due to molecular orbitals localized on sulfur at these energies.…”
mentioning
confidence: 99%
“…This exceptional behavior is due to the evolution of the HOMO-LUMO gap that rapidly decreases with the molecular length, which compensates for the increased tunneling distance. Finally, the last example to be cited with respect to low attenuation factors is the work conducted by Brooke et al, who show a structural control on the electronic transport resonance in HS(CH 2 )n[1,4 −C 6 H 4 ](CH 2 ) n SH (n = 1, 3, 4, 6) metal-molecule-metal junctions, leading to very small attenuation factors [22]. This work offers very promising perspectives in gating the transport resonance in order to modulate the molecular junction behavior.…”
Section: Some Attenuation Factors Of Standard Molecular Junctionsmentioning
confidence: 99%
“…A growing number of software implementations of cDFT are now appearing 1,24,26,29,30,52,[75][76][77][78][79][80] , including linear-scaling implementations designed for application to large systems 18,53 .…”
Section: Conclusion and Summarymentioning
confidence: 99%